Detection of gastrointestinal parasites in Japanese quails (Cortunix cortunix japonica) - Latifi, Nursakinah; Mohd Noor, Mohd Hezmee; Idris, Lokman Hakim; N. M. M., Isa (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
Quails are known for its ability to have high resistance toward common poultry diseases. Therefore, the health status and prevalence of diseases affecting quails is often neglected. One of the most common diseases that affect poultry is endoparasites infection. In Malaysia, currently there is no study or published data in detection of gastrointestinal parasites in Japanese quails. Hence, this study was conducted to detect gastrointestinal parasites in Japanese quails. 30 quails were purchased from Farm X, Malaysia. For this purpose, clinical signs of parasitism were observed through physical examination, fecal examination via Modified McMaster technique, morphological identification via compound microscope and gross lesions via necropsy were performed. Physical examination revealed no clinical signs of parasitism. There was presence of Eimeria oocysts in pooled fecal sample from Farm X. Three common Eimeria species in Japanese quails were found and identified as E. tsunodai, E. uzura and E. bateri. Necropsy revealed normal serosa and mucosa of gastrointestinal tract without presence of any parasites. In conclusion, the presence coccidiasis in this study might indicate natural infection for Japanese quails which beneficial to stimulate immune response in body.